ANALYSIS OF THE DETERMINANTS OF POVERTY IN UNDERDEVELOPED REGIONS OF SUMATRA ISLAND - Badrun Faridz Habibie; Wiwiek Rindayati; Sri Mulatsih (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Sumatra Island has shown a strong economic performance in terms of its contribution to the national GDP. However, the island still has seven underdeveloped regions. This situation is further exacerbated by a high percentage of poverty in each of these underdeveloped areas. This research aims to map the progress of poverty in these underdeveloped regions of Sumatra Island using the Klassen typology, and to analyze the faktors influencing poverty in these regions through panel data regression analysis. The mapping analysis conducted using the Klassen typology consistently places North Nias Regency in the quadrant with a high poverty percentage and low per capita gross regional domestic product (PDRB) throughout the study period. Meanwhile, most other regencies have shifted their quadrant positions. The panel data regression analysis results indicate that significant faktors reducing poverty include the length of well-maintained roads, the Human Development Index (HDI), capital expenditure, and per capita PDRB. On the other hand, the open unemployment rate (TPT) significantly increases poverty. Social assistance spending does not have an effect on poverty in the underdeveloped regions of Sumatra Island.